Modern North American criticism and theory : a critical guide - Wolfreys, Julian, 1958- (Edinburgh University Press, 2006)
Focusing on the growth and expansion of critical trends and methodologies, this book offers an introduction to the literary theory in North America. With essays addressing key figures in their historical and cultural contexts, it depicts the change, transformation, and the quest for and affirmation of multiple cultural voices and identities.